Balancing autonomy and responsibility: the ethics of generating and disclosing genetic information. Issue 2 (1st April 2003) - Hallowell, N; Foster, C; Eeles, R; Ardern-Jones, A; Murday, V; Watson, M
Abstract : Using data obtained during a retrospective interview study of 30 women who had undergone genetic testing— BRCA1/2 mutation searching—this paper describes how women, previously diagnosed with breast/ovarian cancer, perceive their role in generating genetic information about themselves and their families. It observes that when describing their motivations for undergoing DNA testing and their experiences of disclosing genetic information within the family these women provide care based ethical justifications for their actions. Finally, it argues that generating genetic information and disclosing this information to kin raise different types of ethical issues. The implications of these findings for ethical debates about informed choice in the context of genetic testing are discussed.